A comprehensive model of a cavity receiver to achieve uniform heat flux using air-carbon particles mixture. (15th June 2018) - Jin, Yabin; Fang, Jiabin; Wei, Jinjia; Wang, Xinhe
Graphical abstract: Highlights: 2D MCRT-FVM coupling model for the heat transfer process is proposed and developed. The effects of particle density on heat flux and temperature distribution on the receiver are studied. The effects of scattering, absorption, radiation and flow of the air-carbon particles on σ T are analysed. A simple correlation has been proposed to estimate the σ solar caused by L / D, N and Q solar . Abstract: A non-uniform solar flux leads to a non-uniform temperature distribution on the walls of cavity receiver. There exists a large temperature gradient, which can cause great challenges for the safety and high-efficiency operation of concentrating solar power system (CSP). To overcome this problem, micron particles with strong properties of absorption, scatter and radiation are added into the cavity receiver to improve the non-uniform heat flux distribution on the wall. In the present research, a coupled simulation method based on Monte Carlo Ray Tracing (MCRT) method and Finite Volume Method (FVM) is established to simulate the complex photo-thermal conversion process of a two-dimension square solar cavity filled with air-carbon particle mixtures. In the model, first, the solar heat flux distribution on the surface of cavity receiver is simulated by MCRT and the photo-thermal conversion process in the receiver is modeled by FVM. Then both are coupled in the cavity receiver by transferring the absorbed solar energy computed by MCRT to FVM, and this energy is applied as a source term for the energy equation in the FVM part. Based on the coupling model, the thermal performance and the temperature distribution characteristics on the wall of the cavity receiver are studied at various particle densities. The results show that as carbon particle density increases, the heat flux and temperature distribution on the walls of the receiver becomes more uniform and the effects of different L / D and N on σT of the receiver are further investigated.